Characterization of various tandem solar cells: Protocols, issues, and precautions. Issue 2 (10th April 2023) - Park, Jae Hyun; Hwang, Sun Kyung; Ji, Su Geun; Kim, Jin Young
Abstract: In the search for a more efficient solar cell, various types of tandem solar cells (TSCs) have been actively developed worldwide as the performances of the single junction solar cells approach their theoretical limits. Meanwhile, various materials and structures are adopted in TSCs, which makes their characterizations and comparison difficult. Along with the classical monolithic TSC, which exhibits two electrical contacts, devices with three or four electrical contacts have been widely studied as a more performing alternative of commercialized solar cells. For a fair and accurate evaluation of the device performance of TSCs, understanding the effectiveness and limitations of the characterization of the different types of TSCs is crucial. In this paper, we summarize various types of TSCs and discuss their characterization methods. Abstract : Various structures are adopted in tandem solar cells (TSCs) to overcome the efficiency limit of the single junction solar cell. Fair and accurate evaluation of the various TSCs requires understanding the effectiveness and limitations of their characterization methods. Various types of TSCs are summarized. And characterization methods of TSCs are discussed.